Catalytic Asymmetric Synthesis of Cyclohexanes by Hydrogen Borrowing Annulations. Issue 36 (7th August 2019) - Armstrong, Roly J.; Akhtar, Wasim M.; Young, Tom A.; Duarte, Fernanda; Donohoe, Timothy J.
Abstract: Hydrogen borrowing catalysis serves as a powerful alternative to enolate alkylation, enabling the direct coupling of ketones with unactivated alcohols. However, to date, methods that enable control over the absolute stereochemical outcome of such a process have remained elusive. Here we report a catalytic asymmetric method for the synthesis of enantioenriched cyclohexanes from 1, 5‐diols via hydrogen borrowing catalysis. This reaction is mediated by the addition of a chiral iridium(I) complex, which is able to impart high levels of enantioselectivity upon the process. A series of enantioenriched cyclohexanes have been prepared and the mode of enantioinduction has been probed by a combination of experimental and DFT studies. Abstract : A catalytic asymmetric method is described for the synthesis of enantioenriched cyclohexanes from racemic 1, 5‐diols by hydrogen borrowing catalysis. This reaction is mediated by a chiral iridium(I) complex which is able to impart high levels of enantioselectivity to the process.